Correlation between Hyperuricemia and Severity of Coronary Artery Disease Detected by Coronary Angiography in Men and Women - Mohammed Madbouly; Ahmed Boghdady; Yasser Abd El Hady; Khaled Abd El Meguid (Egyptian Journal of Medical Research, 2022)
The association between serum uric acid and ischemic heart disease remains controversial and serum uric acid has not yet been established as cardiovascular risk factor. Our objective was to study the association of serum uric acid level with angiographic severity of coronary artery disease in males and females with ischemic heart disease. This observational study was conducted on two hundred patients divided into one hundred male patient, subdivided into fifty patient with elevated SUA and fifty patient with normal SUA and one hundred female patient subdivided into fifty patient with elevated SUA and fifty patient with normal SUA underwent coronary angiography for detection of CAD in cath lab unit of cardiology department of Beni-Suef and Sohag university. The severity of CAD was assessed on the basis of Gensini score and clinical vessel score. For all groups, conventional risk factors, levels of serum uric acid, and other biochemical markers were assessed.